Urinary tract Infection in Female Patients Visiting Tertiary Care Hospital and Determination of ESBL Producing MDR Isolates (Tribhuvan University Journal of Microbiology, 2022)
Objectives: The main purpose of this study was to assess the urinary tract infection (UTI) in female patients and determine the extended spectrum of beta-lactamase producers among MDR isolates.Methods: A three-month hospital-based cross-sectional study was conducted from Marchto April 2022 at the Microbiology laboratory of Alka hospital, Lalitpur. Following the standard protocol, urine samples were taken for culture and identification. Urine samples were cultured using a semi-quantitative approach and antimicrobial susceptibility test was performed by disc diffusion method.Results: Out of 493 female urine samples examined, significant growth was found in 106 samples. The positive isolates belonged to 5 different species. Out of them E.coli (77.36%) was the major pathogens isolated followed by Klebsiella pneumoniae (6.61%), Klebsiella oxytoca and Pseudomonas aeruginosa (1.88%) as Gram negative bacteria. And the most common Gram positive bacteria was found to be Staphylococcus aureus (12.26%). The most effective drug for Gram negative isolates was Amikacin (93.396%) followed by Nitrofurantoin (91.505%). The least effective drug against Gram negative bacteria was found to be Cefexime (64.16%) and Amoxicillin (58.49%). And for Gram positive isolates Ceftazidime (100%) and Amikacin (100%) were the choice of drug showing high susceptibility. The least effective drug used against Gram positive isolates tends to be Cloxacillin (15.38%). Out of 106 isolates 63 were found to be multidrug resistant among which 31 of them were ESBL producers confirmed by cephalosporin/clavulanate double disc synergy method. The urinary tract infection was most common in the age group 20-30 (20.75%) followed by age group 30-40 (16.98%).Conclusion: UTI was least common among age groups 0-10 and 80-90 years. Bacterial isolates causing UTI had variation in the antibiotic susceptibility pattern with resistance against commonly used antibiotics which is a serious concern.